Winter Street - Book 1 - Hilderbrand, Elin. (New York : Back Bay Books, 2023)
Kelley Quinn is the owner of Nantuckets Winter Street Inn and the proud father of four, all of them grown and living in varying states of disarray. Patrick, the eldest, is a hedge fund manager with a guilty conscience. Kevin, a bartender, is secretly sleeping with a French housekeeper named Isabelle. Ava, a school teacher, is finally dating the perfect guy but cant get him to commit. But when Bart, the golden child and a recent Dartmouth graduate, announces that he has joined the Marines and is leaving for Afghanistan two days before Christmas, Mitzi is so distressed that she confesses to having an affair with a long-time guest at the Inn. As more secrets unravel and chaos ensues, its up to Ava to piece together the holiday before everyone leaves, possibly forever.
Keywords: Dysfunctional families -- Fiction; Families; Massachusetts; Nantucket Island; Fiction; Bed and breakfast accommodations; Massachusetts; Nantucket Island; Fiction; Family reunions -- Fiction; Triangles (Interpersonal relations) -- Fiction; Nantucket Island (Mass.) -- Fiction; Domestic fiction; Christmas fiction; Romance fiction; Fiction